The IT Identity Threat: A Conceptual Definition and Operational Measure. Issue 1 (2nd January 2019) - Craig, Kevin; Thatcher, Jason Bennett; Grover, Varun
Abstract: As individuals' relationships with information technology (IT) grow more complex and personal, our understanding of the problem of resistance to IT continues to evolve. Current approaches to resistance are based on perceived threats to work tasks and social structure. This work enhances our understanding of resistance by developing a definition and measure of the IT Identity Threat, a new construct that integrates social, task-related, and personal factors of resistance. Grounded in identity theory, the IT Identity Threat offers a parsimonious means to explain and predict IT resistance behaviors. Using data from two independent studies conducted among students and faculty at a large university in the Southeastern United States, we validate an operational measure of IT Identity Threat as a second-order construct and demonstrate that it successfully predicts resistance to IT. Our findings provide support for the IT Identity Threat construct as a simple mechanism to study resistance to IT.